Compact complex surfaces - Barth Wolf P; de Ven Antonius Van; Hulek Klaus; Peters Chris A M (Berlin Springer-Verlag, 1984)
The first edition of Compact Complex Surfaces was published in 1984 and has become one of the most important books on the subject. In this second enlarged edition the major developments of the last 20 years have been incorporated. The Enriques-Kodair
Keywords: Complex surfaces; Differential geometry